Legal Strategies How Corporations Use Law to Improve Performance - Masson, Antoine; Shariff, Mary J.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2009)
Far from regarding the law as supreme, corporations approach law as an element of executive thought and action aimed at optimizing competitiveness. The objective of this book is to identify, explore and define corporate legal strategies that seek advantage in the opportunities revealed when the Law is perceived as a resource to be mobilized and aligned with the firm$1 (Bs business and economic agendas.s
Theorizing Legal Strategies -- From Legal Monitoring to Legal Core Competency: How to Integrate the Legal Dimension into Strategic Management -- The Origin of Legal Opportunities -- A Theory of Legal Strategy -- Alternative Conceptions of Legal Strategy and Strategic Legal Interpretation -- The Crucial Role of Legal Capability in the Realisation of Legal Strategies -- Litigation Cost Strategies from Economics -- A Cognitive Approach to Judicial Strategies: A Perspective from the French Business Environment -- Legal Strategies In Action -- Perspectives on Legal Strategy through Alternative Dispute Resolution -- Strategic Planning to Avoid Organizational Criminal Liability: A Canadian Perspective -- Corporate Risk Management and Legal Strategy -- A Legal Strategy Case Study: Trusts in Securitization -- Activist Hedge Funds and Legal Strategy Devices -- Patents and Trademarks: From Business Law to Legal Astuteness -- The Strategic Use of Legal Margins: How to Introduce an Extension of Someone Else$1 (Bs Brand -- The Effect of Complexity of Law on Litigation Strategy -- Evidence Collection as a Legal Resource for Strategy: A French and European Perspective -- Transnational Transactions: Legal Work, Cross-Border Commerce and Global Regulation -- Responses To Legal Strategies -- Limits to Horizontal Strategies: Majority Shareholders Facing Minority Activism -- Innovation and Access: Legal Strategies at the Intellectual Property Rights and Competition Law Interface -- Conclusion: Enlarging The Potential For A (3z(BLaw And Strategies(3y (BApproach -- Applied Advanced Legal Strategy in Court: The Example of the International Criminal Court.s
Keywords: Law; Civil law; International law; Trade; Law and economics; Law; Civil Law; International Economic Law, Trade Law; Law and Economics; Electronic books